Fine Motor Skills Enhance Lexical Processing of Embodied Vocabulary: A Test of the Nimble-Hands, Nimble-Minds Hypothesis. Issue 10 (October 2017) - Suggate, Sebastian; Stoeger, Heidrun
Research suggests that fine motor skills (FMS) are linked to aspects of cognitive development in children. Additionally, lexical processing advantages exist for words implying a high body–object interaction (BOI), with initial findings indicating that such words in turn link to children's FMS—for which we propose and evaluate four competing hypotheses. First, a maturational account argues that any links between FMS and lexical processing should not exist once developmental variables are controlled for. Second, functionalism posits that any link between FMS and lexical processing arises due to environmental interactions. Third, the semantic richness hypothesis argues that sensorimotor input improves lexical processing, but predicts no links between FMS and lexical processing. A fourth account, the nimble-hands, nimble minds (NHNM) hypothesis, proposes that having greater FMS improves lexical processing for high-BOI words. In two experiments, the response latencies of preschool children ( n = 90, n = 76, ages = 5;1) to 45 lexical items encompassing high-BOI, low-BOI, and less imageable words were measured, alongside measures of FMS, reasoning, and general receptive/expressive vocabulary. High-BOI words appeared to show unique links to FMS, which remained after accounting for low-BOI and less imageable words, general vocabulary, reasoning, and chronological age. Although further work is needed, the findings provide initial support for the NHNM hypothesis.